A Versatile Tool for Haptic Feedback Design Towards Enhancing User Experience in Virtual Reality Applications - Vasilije Bursać; Dragan Ivetić (Applied Sciences)
The past 15 years of extensive experience teaching VR system development has taught us that haptic feedback must be more sophisticatedly integrated into VR systems, alongside the already realistic high-fidelity visual and audio feedback. The third generation of students is enhancing VR interactive experiences by incorporating haptic feedback through traditional, proven, commercially available gamepad controllers. Insights and discoveries gained through this process contributed to the development of versatile Unity custom editor tool, which is the focus of this article. The developed tool supports a wide range of use cases, enabling the visual, parametric, and descriptive creation of reusable haptic effects. To enhance productivity in commercial development, it supports the creation of haptic and haptic/audio stimulus libraries, which can be further expanded and combined based on object-oriented principles. Additionally, the tool allows for the definition of specific areas within the virtual space where these stimuli can be experienced, depending on the virtual object the avatar holds and the activities they perform. This intuitive platform allows the design of reusable haptic effects through graphical editor, audio conversion, programmatic scripting, and AI-powered guidance. The sophistication and usability of the tool have been demonstrated through several student VR projects across various application areas.